2020
DOI: 10.1111/aej.12413
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of the maxillary sinus floor during apical surgery of maxillary molars: A retrospective analysis using cone beam computed tomography

Abstract: This retrospective analysis assessed a possible correlation of perforation of the maxillary sinus floor during apical surgery of maxillary molars and the distances from the treated apices/periapical radiolucencies to the sinus floor. The material included 168 apical surgeries of maxillary first or second molars performed from 1999 to 2016. In 22 (out of 33) perforation cases, a preoperative cone beam computed tomography (CBCT) was available. These cases were defined as the test group. From the pool of operated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…In contrast, two other studies using periapical radiographs for assessment, reported that the coronal extent of root-end filling (≤2 mm vs. >2 mm) had no significant influence on periapical healing (Barone et al, 2010;Villa-Machado et al, 2013). Similarly, von Arx, Kach, et al (2020) reported that the coronal extent of MTA root-end fillings and their width, as well as the residual peripheral root dentine thickness did not have any significant influence on periapical healing outcome. However, it is worth noting that the surgeries were performed by an experienced oral surgeon and the mean coronal extent of root-end filling was only 2.02 ± 1.24 mm (range: 0.78-3.80 mm).…”
Section: Effect Of Apical Resection Bevel Root-end Cavity Preparation...mentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, two other studies using periapical radiographs for assessment, reported that the coronal extent of root-end filling (≤2 mm vs. >2 mm) had no significant influence on periapical healing (Barone et al, 2010;Villa-Machado et al, 2013). Similarly, von Arx, Kach, et al (2020) reported that the coronal extent of MTA root-end fillings and their width, as well as the residual peripheral root dentine thickness did not have any significant influence on periapical healing outcome. However, it is worth noting that the surgeries were performed by an experienced oral surgeon and the mean coronal extent of root-end filling was only 2.02 ± 1.24 mm (range: 0.78-3.80 mm).…”
Section: Effect Of Apical Resection Bevel Root-end Cavity Preparation...mentioning
confidence: 95%
“…The perceived problem is related to the risk of Schneiderian membrane perforation, potentially resulting in maxillary sinusitis and compromised periapical healing. The reported incidence of maxillary sinus perforation during root‐end surgery ranges from 10% to 50% (Oberli et al, 2007) with a higher risk when separated by less than 1 mm (von Arx, Kach, et al, 2020). Apart from post‐operative nose bleeding, four of the six teeth with maxillary sinus perforation displayed complete healing, 1 year post‐operatively, and none of them displayed altered physiology of the maxillary sinus (Taschieri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Se han realizado investigaciones sobre la relación entre las raíces de los dientes posteriores y las estructuras anatómicas importantes para el procedimiento de cirugía apical mediante TCHC (6,9,10), así como del riesgo de perforación del seno maxilar (11). En contraste, solo hay dos investigaciones realizadas sobre la relación entre los dientes del sector from the root to the palatal bone table.…”
Section: Introductionunclassified
“…Many authors, in different cadaveric and radiographic studies, have shown the proximity between the root apices of the maxillary posterior teeth and the sinus floor [17][18][19]. This can lead to accidental oroantral communication during various stages of the surgery [20]. Hauman et al have shown that the invasion of a healthy maxillary sinus does not appear to cause a permanent alteration of its physiological function because the sinus mucosa regenerates five months after its surgical removal [21].…”
Section: Introductionmentioning
confidence: 99%